Robust hierarchically interconnected porous carbons derived from discarded Rhus typhina fruits for ultrahigh capacitive performance supercapacitors - Wei, Xianjun; Wei, Ji-Shi; Li, Yongbin; Zou, Hongli (Journal of power sources, 2019)
An efficient and economic approach for sustainable production of hierarchically interconnected porous carbons are designed and fabricated through the pyrolysis of Rhus typhina fruits and followed by KOH activation to create micropores or mesopores on the nano-sheet wall of macropores. The related N-doped carbon consists of a plenty of micropores and owns high specific surface area (up to 2675 m2 g−1), resulting in high performances for supercapacitors, such as ultrahigh specific capacitance (568 F g−1 at 1 A g−1), remarkable rate capability (310 F g−1 at 20 A g−1, 282 F g−1 at even 30 A g−1 current density) and good long-term stability (capacitance retention of 99% after 10000 cycles at 30 A g−1) in 1 mol L−1 H2SO4. Moreover, the carbon derived from Rhus typhina fruits demonstrates 474 F g−1 at 1 A g−1, 281 F g−1 at 30 A g−1, and capacitance retention of 92% after 10000 cycles at 30 A g−1 in 6 mol L−1 KOH electrolyte. This novel and sustainable biomass-derived carbon material holds a bright future for fabricating high energy supercapacitors. [Display omitted] •RTFs based carbon exhibits ultrahigh capacitance of 568 F g−1 at 1.0 A g−1.•Graphene like sheets built a hierarchical interconnected porous microstructure.•Functional groups induce Faraday reactions, and generate pseudocapacitance.•Biomass wastes provide sustainable and cheap raw materials for supercapacitors.